Implementation of QR Code in A Student Attendance Information Based On WhatsApp Gateway - Harlin Feby Karnita Sumbaluwu; Dwi Shinta Angreni; Mohammad Yazdi Pusadan; Chairunnisa Lamasitudju; Nouval Trezandy Lapatta (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
The attendance information system at Senior High School 7 Sigi, still uses a manual attendance system, namely writing on paper sheets. The problem that often occurs is the loss of student attendance books which causes the school to have difficulty in recapitulating attendance and also reporting attendance to parents. Another problem that occurs due to manual attendance is that parents cannot directly monitor their children's attendance at school which causes some students to skip school. The recommended solution is to use an attendance information system by utilizing QR Code technology so that student attendance is more practical and also the data storage is much safer. WhatsApp Gateway is used as a monitoring medium for parents because this system will send notifications via the WhatsApp application every time the lesson starts, effectively and in real-time. This attendance system uses the Waterfall method which starts from the planning, analysis, design and implementation stages